Associated Between Pregnancy Age, Body Length and Weight of Newborn in High Risk Pregnancy - Indah Rohmawati; Evi Tunjung Fitriani; Anis Murniati (Indonesian Journal of Global Health Research, 2023)
Every newborn is expected to be born on time at 37-42 weeks (term), so that all organs have experienced maturity and have normal length and weight. The phenomenon found in the field is that even though babies are born on time, babies are still born with body weight and length that have not reached the expected standard, which in the future can be predicted to experience stunting. The purpose of this research is to analyze the relationship between gestational age, body length and newborn weight in high risk pregnancy. This type of observational analytic research, cross-sectional design. The study population was all mothers who gave birth in Tulungagung Regency. Inclusion criteria Maternal pregnancy is classified as high risk and will receive assistance in 2022. The sample is 135 respondents. The research was carried out in the Tulungagung district from August to December 2022. Data was collected by calculating the gestational age and measuring the body length and weight of newborns. data were analyzed using the Pearson Product Moment test. The results showed that gestational age can affect newborn weight with a p value of 0.001 with a weak relationship level of 0.281. While the length of the newborn's body has nothing to do with gestational age, however, the newborn's weight is significantly related to the p value of 0.000.